دور النشاط المدرسي في التحصيل الدراسي - عزابي, سمية (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة التعرف على النشاط المدرسي ودوره في التحصيل ألدراسي, حيث يعتبر النشاط المدرسي بأنه نشاط يقوم به المتعلمين يهدف إلى إحداث نمو في جميع الجوانب المعرفية والعلمية والنفسية والتربوية للمتعلمين, ويتم داخل المدرسة وخارجها, إلا أنه يكون وفق منهج مدرسي وخطط وأهداف تربوية محددة The purpose of this study is to make known what is the school activity and its role in the acquisition of knowledge, this activity is a practice performed by learners, it aims to achieve progress in all sides of the knowledge scientific, psychological and educational of learners, within the school and elsewhere according to a program, plans and objectives.
مقال بمجلة السراج في التربية وقضايا المجتمع . مج 05 ع01. فيفري 2021 . جامعة الوادي
Keywords: الدور, النشاط , المدرسي , التحصيل , الدراسي; role, School, activity, Academic, achievemen